Evaluation of vaccination status of children attending a private tertiary paediatric hospital in urban Hyderabad - Seethamraju, Rajasri; Kharidehal, Neelima; Koyalakonda, Chandrashekhar; Maddukuri, Pallavi; Rayudu, Vamsi Kiran (Indian Journal of Child Health, 2018)
Objectives: The objectives of this study were to understand the vaccination status and reasons for missed vaccination in the catchment of a tertiary private paediatric hospital in a densely populated area in urban Hyderabad. Study Design: This was a questionnaire-based cross-sectional survey. Methods: Data regarding the vaccinations for all the vaccines included in the guidelines provided by the Indian Academy of Pediatrics were collected from eligible parents attending the outpatient department after informed consent. Results: Vaccination coverage was almost 90% with private health facilities being used by both timely and missed vaccine groups. Factors such as gender bias, large families, or low educational status were absent in both groups in this urban population unlike rural populations. Vaccines perceived by the parents as optional and booster doses were most often missed and an unwell child was the most common reason for the missed vaccines. Conclusion: Even in urban areas like our densely populated catchment, specified dates for next vaccine at each visit to the pediatrician will improve timely vaccination. Awareness also needs to be raised regarding the importance of what are perceived to be optional vaccines.